Effect of organic montmorillonite on the hot storage stability of asphalt modified by waste packaging polyethylene. Issue 2 (26th June 2014) - Fang, Changqing; Zhang, Ying; Yu, Ruien; Liu, Xiaolong; Hu, Jingbo; Zhang, Maorong
Abstract : In this paper, waste polyethylene (WPE), a large class of waste plastic packaging, and organic montmorillonite (OMMT) were employed as the polymer modifier and additive to modify base asphalt, and then hot storage stability of modified asphalt was studied. Structure of the modified asphalt was characterized with X‐ray diffraction and fluorescence microscopy. Moreover, the hot storage stability of WPE‐modified asphalt was investigated by Fourier‐transform infrared analysis, differential scanning calorimetry, and thermal gravimetry. Results show that an exfoliated structure is formed in the modified asphalt after adding OMMT. The WPE modifier particles become smaller and are more uniformly dispersed in the modified asphalt system after adding OMMT. Also, the addition of OMMT effectively improves the hot storage stability of the modified asphalt. The OMMT not only increases the compatibility between the WPE modifier and base asphalt but enhances the homogeneity of the modified asphalt at extreme temperatures. Heat capacity and phase behavior of modified asphalt after adding OMMT are changed; in the meantime, the thermal stability of the modified asphalt increases. J. VINYL ADDIT. TECHNOL., 21:89–93, 2015. © 2014 Society of Plastics Engineers